2021
DOI: 10.2139/ssrn.3877195
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Future Changes in Photovoltaic Potential Over East Asia?

Abstract: Heavily industrialized East Asia, with its high greenhouse gas emissions, must inevitably increase renewable energy production to achieve the goals of the Paris Agreement. Photovoltaics (PV), a widely utilized renewable energy source, is directly affected by the weather and climate. This study conducted the first analysis of current and future PV potential (PVpot) changes over East Asia using the ERA5 reanalysis and multiple high-resolution regional climate model simulations. The recent PVpot over East Asia di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…, where is surface down-welling shortwave radiation. represents the RSDS under standard test conditions, and equals to 1000 W/ according to the International Electrotechnical Commission (IEC) 61215 standard (Park et al, 2022). indicates the performance ratio:…”
Section: Photovoltaic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…, where is surface down-welling shortwave radiation. represents the RSDS under standard test conditions, and equals to 1000 W/ according to the International Electrotechnical Commission (IEC) 61215 standard (Park et al, 2022). indicates the performance ratio:…”
Section: Photovoltaic Potentialmentioning
confidence: 99%
“…Previous studies revealed that RCM simulations within CORDEX-EA-II have the ability to simulate the air temperature, precipitation and extreme events (Yu et al, 2020(Yu et al, , 2021Yang et al, 2019), and this study further investigates the simulated PVpot. (Park et al, 2022). Computed based on the same atmospheric variables from RCMs, the simulated PVpot is interpolated to 0.25°×0.25° grids for easy comparison with ERA5.…”
Section: Introductionmentioning
confidence: 99%